Local Schrödinger flow into Kähler manifolds - Ding, Weiyue; Wang, Youde (Science China. Mathematics, 2001)
In this paper we show that there exists a unique local smooth solution for the Cauchy problem of the Schrödinger flow for maps from a compact Riemannian manifold into a complete Kähler manifold, or from a Euclidean space Rm into a compact Kähler manifold. As a consequence, we prove that Heisenberg spin system is locally well-posed in the appropriate Sobolev spaces.